Analysis Of Pseudoelastic Deformation Cycles Of Gradiently Aged Niti Shape Memory Alloys - Ishak, Muhammad Hanafi (Universiti Sains Malaysia, 2021)
Functionally graded NiTi shape memory alloy is a modification of the alloy to have a continuous varying thermomechanical property by expanding the transformation interval such as transformation stress and temperature window. In this study, a functionally graded NiTi wire was created with an optimum pseudoelastic behaviour through a gradient ageing treatment. Gradient ageing furnace was built to age the wire in a gradient temperature profile. The aged specimens were test with the Differential Scanning Calorimetry (DSC) to observe and analyse the transformation temperature of graded NiTi wire. The pseudoelastic behaviour of the functionally graded NiTi was analysed by conducting tensile test with cyclic load in room temperature. As the result, the gradient aged specimen exhibited forward and reverse stress gradient of 1.42GPa and 2.52GPa respectively with residual strain of 2.7%. For the cyclic deformation, reduction in the forward and reverse transformation stress was observed. Plateau and residual strain were affected from the cyclic loading deformation. Residual strain tends to stabilize asymptotically in the later cycles compared to the earlier one. Thus, make the graded NiTi have a good psuedoelastic behaviour upon cyclic deformation compared to the original wire and isothermal aged wire.